An ultra-thin quad-band metamaterial inspired absorber using symmetric bent-arrow shaped resonator for sensing and imaging in defense applications - Raghvenda Kumar Singh; Ashish Gupta; Anand Sharma; Utkarsh Tyagi; Nishchay Gupta; Akash Yadav (Materials Research Express, 2020)
In this paper, a novel compact quad-band polarization insensitive metamaterial absorber has been proposed to be employable in the microwave frequency regime. The unit-cell geometry comprises of four symmetric bent-arrow shaped resonators, where each arrow has been bounded by an open ring. The resultant structure is further surrounded by a closed ring to obtain an extra resonance band. Full-wave simulation with normal incidence depicts quad-band operation with absorption peaks at 3.24 GHz (S-band), 6.55 GHz (C-band), 15.22 GHz (Ku-Band), 15.94 GHz (Ku-band) and absorptivity levels of 99.57%, 99.94%, 96.10%, 98.65% correspondingly. It also shows full width half maximum (FWHM) bandwidth of 100 MHz, 200 MHz and 1210 MHz in the first, second and third bands respectively. Furthermore, the proposed structure is based on four-fold symmetry therefore exhibits polarization-insensitive behaviour unlike conventional absorbers. The structure is fabricated on 1 mm FR4 Glass Epoxy substrate equivalent to 0.0108 λ _0 hence, can be used as absorber coating for planar surfaces. The designed absorber has been fabricated and experimental results were in good agreement with the simulated responses enabling its wide application in various technologies like stealth technology, radar cross section reduction, anechoic chambers, electromagnetic interference/electromagnetic compatibility, and radio frequency identification.